Searching for a universal indicator of plant stress: a three-year study of three woody species in three environmental gradients in boreal forests - Kozlov, Mikhail V.; Zverev, Vitali; Zvereva, Elena L. (Springer Science and Business Media LLC, 2025)
Stress in plants refers to adverse changes in their functioning. The occurrence and intensity of a stress can be assessed by alterations in plant traits, termed stress indicators. The ultimate goal of this study was to test whether six morpho-physiological plant traits, frequently used as stress indicators, respond consistently across species to various environmental stressors, with the aim of detecting universal stress indicators in forest tree species. We examined changes in vertical increment, leaf/needle size, shoot length, needle longevity, photosynthetic efficiency and fluctuating asymmetry in three common European tree species, mountain birch (Betula pubescens var. pumila), Norway spruce (Picea abies) and Scots pine (Pinus sylvestris) along three environmental gradients (elevation, pollution and seashore) from forests to stressful open environments. Data were collected in 2003, 2004 and 2005 from 297 trees growing naturally across 36 sites in north-western Russia. Fluctuating asymmetry was the only trait that did not vary among sites with differing levels of environmental stress. Leaf/needle size and shoot length occasionally changed along stress gradients, but the magnitude and direction of these changes differed by gradient type and species, resulting in no significant overall stress effect for either trait. In contrast, photosynthetic efficiency, vertical increment and needle longevity consistently decreased from low-stress to high-stress sites. The overall effect was significant for each of these three traits despite the magnitudes of these decreases differed depending on the gradient type and location, species, study year and individual tree. Replication at spatial, temporal and taxonomic levels ensured the robustness and reliability of our results that photosynthetic efficiency, vertical growth and needle longevity reliably captured a general stress syndrome and may serve as stress indicators in forest species.